Distribusi dan Kemelimpahan Spesies Tumbuhan Bawah pada Naungan Pinus mercusii,Acacia auriculiformis danEucalyptus alba di Hutan Gama Giri Mandiri, Yogyakarta - Nahdi, Maizer Said; Darsikin, Darsikin (Jurnal Natur Indonesia, 2014)
The purpose of this research was to study distribution and abundance of (shrubs, herbs, and rumput) under the three stands,i.e. Pinus mercusii, Acacia auriculiformis and Eucalyptus alba and environmental factors influencing them in Gama Girimandiri Forest. Data were collected in April-May 2011, using square plots. Plots were located in three locations by followinga stratified random sampling method. We administered 10 repetitions, and plot size 5x5 m for shrubs and herbs, and 1X1 m forgrass. The species found in each stand were identified and calculated for their density, frequency, domination, importantvalue, diversity index, and those parameters’ correlation with the measured environmental factors. The study shows that 59species of herbs and shrubs, and 12 species of grass. In the three stands, it could be shown various domination of grass,meanwhile there is no dominant species at the level of herbs and shrubs. The highest density, measured by diversity index,was observed at the stand of Pinus (3,13), followed by Acacia (3,12) and Eucalyptus (2,8). The distribution and density ofMemecylon sp and Oplismenus burmanni were observed at their highest value under the stand of Pinus, Lantana camaraLinn (37.2). At the same fashion, Paspalum conjugatum (58.3) does under the stand of Acacia, and Desmodium triflorum(64,2) and Ischaemum magnum (122) under Eucalyptus. Lantana camara could always be found under the three stands, ithad high important value, categorized as strategy species and invasive. Light density and pH significantly influenced thediversity index of shrubs and herbs. In addition, only soil temperature gave an effect to grass.